BAG ATO-ASPECT AND MODERNIZATION OF EDUCATIONAL OF THE EDUCATIONAL PROCESS IN FOREIGN LANGUAGE CLASSES IN FRAMEWORK OF PERSONALITY-ORIENTED PARADIGM IN TECHNICAL HIGH SCHOOL - A.V. Lityahina (Academy of Cognitive and Natural Sciences, 2008)
The main aspects of educational-upbringing process in the university within personality orientedparadigm are described in détails in the articleю